The complexities of prior record, current crime type, and Hukou status in China: interactive effects in sentencing. (2nd January 2016) - Lao, Jiaqi
Abstract : Using sentencing data all over China from 2000 to 2011, this study examines the complex relationship between offenders' prior record, current offense, hukou status and sentencing outcomes. Based on the perspectives and findings of previous studies conducted in common-law jurisdictions, this study suggests that prior record influences sentencing decisions in a complex manner and the number of prior conviction as a measure of prior record is not adequate. Furthermore, it also appears that the prior record effects are contingent upon current offense type, carrying more weight on the less serious current crime compared to more serious current crime. Finally, after illustrating the existence of sentencing disparity based on hukou status, this study uncovers that the interactive effects between prior record and hukou discrimination are dependent on the current offense type in China.